Tax education in the era of Information and Communication Technology (ICT): conceptual vs. technical / Nurul Hidayah Ahamad Nawawi and Lai Ming Ling - Ahamad Nawawi, Nurul Hidayah; Ming Ling, Lai (2010)
Tax education in the 21st century faces significant challenges on how to educate accounting graduates (future accountants) in a complex and rapidly changing environment in the era of lCT (Howieson, 2003; Ismail, 2003). The advancement of ICT has changed the way people work and how organizations are structured, managed and operated. However, many research claimed that current tax curriculum failed to equip future accounting graduates with necessary tax knowledge and technical skills as well as ICT skills in order to perform competently in practice (Howieson, 2003; Lai, 2008; Miller & Woods, 2000; Ott & Donnelly, 1999; Tan & Veal, 2005). Therefore, there is a need to examine whether the existing content coverage of tax courses is adequate to prepare accounting students for the tax practice in the era of ICT. In fact, this is important to ensure that graduates are ready for the rapid changes in the business environment, in order to become a knowledge worker. Nonetheless, at the time of study, little is known if accounting graduates are well equipped with the conceptual and technical knowledge in taxation as well as the relevant ICT skills needed in tax practice?